Contemporary Issues in Head and Neck Cancer Management - Marcu, Loredana G. (IntechOpen, 2015)
While the management of head and neck cancer has evolved over the last few decades, there are still several challenges and unanswered questions that need solutions. This book is a small compilation of some topical aspects regarding head and neck cancer treatment, including the etiology of HPV-positive oropharyngeal cancers and risk factors in the young population, the challenge of surgical margin definition and the perennial problem of systemic treatment due to distant metastases. Radiobiological aspects are also covered through the Rs of radiotherapy, with a couple of chapters being dedicated to radioresistance and tumour microenvironment. Contemporary Issues in Head and Neck Cancer Management comes as an addition to the existing literature that aims to tackle this radiobiologically challenging tumour.